Gain control in L-band erbium-doped fiber amplifier using a ring resonator - Harun, Sulaiman Wadi; Tamchek, Nizam; Poopalan, Prabakaran; Ahmad, Harith (IOP Publishing, 2002)
Gain control in a long-wavelength (L-band) erbium-doped fiber amplifier (EDFA) using a counter-propagating ring resonator is demonstrated. The clamped gain can be controlled to be in the range from 7.0 to 18.0 dB for the 1580 nm signal at -30 dBm by tuning the oscillating laser in the range from 1565 to 1540 nm. The design prevents oscillating light from being coupled out, but it degrades the amplifier's noise figure and signal gain as the dynamic range is increased.